2010
DOI: 10.1111/j.1432-2277.2009.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor beta chain (TCR-Vβ) repertoire of circulating CD4+CD25−, CD4+CD25lowand CD4+CD25highT cells in patients with long-term renal allograft survival

Abstract: Summary The mechanisms underlying maintenance of renal allografts in humans under minimal or conventional immunosuppression are poorly understood. There is evidence that CD4+ CD25+ regulatory T cells and clonal deletion, among other mechanisms of tolerance, could play a key role in clinical allograft survival. Twenty‐four TCR‐Vβ families were assessed in CD4+ CD25−, CD4+ CD25low and CD4+ CD25high T cells from patients with long‐term renal allograft survival (LTS), patients exhibiting chronic rejection (ChrRx),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Concerning the particular cell types involved, several studies have discussed the role of T-cell receptors (TCRs) in transplant rejection. Velásquez et al (8) suggested that differential expression of particular TCR β chain variable families and high levels of circulating CD4(+) CD25 (high) T cells in long-term surviving renal transplant patients contribute to an active and specific state of immunologic suppression. Matsutani et al (9) indicated that the skew in TCR usage was correlated with the levels of clonal T-cell expansion, indicating that the expanding T cells were responsible for the skew in TCR usage.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the particular cell types involved, several studies have discussed the role of T-cell receptors (TCRs) in transplant rejection. Velásquez et al (8) suggested that differential expression of particular TCR β chain variable families and high levels of circulating CD4(+) CD25 (high) T cells in long-term surviving renal transplant patients contribute to an active and specific state of immunologic suppression. Matsutani et al (9) indicated that the skew in TCR usage was correlated with the levels of clonal T-cell expansion, indicating that the expanding T cells were responsible for the skew in TCR usage.…”
Section: Introductionmentioning
confidence: 99%